1. Start with the two equations:
7y + 6 = 5x
4y + 4 = 3x
2. Rearrange them to isolate terms involving \(x\) and \(y\) on one side of the equation:
5x - 7y = 6
3x - 4y = 4
3. Multiply the second equation by 5 and the first equation by 3 to make the coefficients of \(x\) equal:
15x - 21y = 18
15x - 20y = 20
4. Subtract the second equation from the first:
(15x - 21y) - (15x - 20y) = 18 - 20
-y = -2
y = 2
5. Substitute \(y = 2\) back into the second equation to find \(x\):
4(2) + 4 = 3x
8 + 4 = 3x
12 = 3x
x = 4
Thus, the solution to the equations is:
y = 2
x = 4